The Influence of Business Location and Word of Mouth on Purchasing Decisions - Sudirjo, Frans; Paramita, Catarina Cori Pradnya; Yani, Indri; Marjuki, Marjuki; Utami, Eva Yuniarti (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
A strategic business location that is close to the target market is one of the factors that researchers believe can influence consumer purchasing decisions. This close location will make consumers decide to purchase, be satisfied, and communicate with other consumers to encourage enthusiastic other consumers to share purchasing decisions with producers who have sales points in strategic locations. Therefore, this research aims to analyze the influence of business location and word of mouth on consumer purchasing decisions. This research is quantitative research with an explanatory approach that uses a questionnaire method in collecting data. The questionnaire was distributed to Indomaret and Alfamart consumers spread throughout Indonesia with the criteria of having shopped at least 3 times. The questionnaire contains statements of agree, strongly agree, disagree, strongly disagree, and neither agree nor the same on the 16 question items asked. The result thi research show the Business Location variable can have a positive relationship and a significant influence on Purchasing Decisions because the P-Values value is positive and is below the significance level of 0.036. This is in line with the researcher's statement and the direction of the questionnaire questions above which shows that a strategic business location can increase purchasing decisions because it is easy to reach, close, and does not take a lot of time. Thus, the first researcher's hypothesis and beliefs can be justified and accepted. Apart from that, the results of the second research hypothesis and beliefs also show the same results if the Word of Mouth variable has a positive relationship and a significant influence on Perchase Decision because the P-Values value is positive and is below the 0.05 significance level, namely 0.029. It is reasoned that word of mouth or word of mouth communication between consumers can increase purchasing decisions and enthusiasm between consumers. Keywords: Business Location, Word of Mouth, Purchase Decision